Biodegradable, pH-sensitive chitosan beads obtained under microwave radiation for advanced cell culture - Piątkowski, Marek; Janus, Łukasz; Radwan-Pragłowska, Julia; Bogdał, Dariusz; Matysek, Dalibor (Colloids and surfaces. B, Biointerfaces, 2018)
A new type of promising chitosan beads with advanced properties were obtained under microwave radiation according to Green Chemistry principles. Biomaterials were prepared using chitosan as raw material and glutamic acid/1,5-pentanodiol mixture as crosslinking agents. Additionally beads were modified with Tilia platyphyllos extract to enhance their antioxidant properties. Beads were investigated over their chemical structure by FT-IR analysis. Also their morphology has been investigated by SEM method. Additionally swelling capacity of the obtained hydrogels was determined. Lack of cytotoxicity has been confirmed by MTT assay. Proliferation studies were carried out on L929 mouse fibroblasts. Advanced properties of the obtained beads were investigated by studying pH sensitivity and antioxidant properties by DPPH method. Also susceptibility to degradation and biodegradation by Sturm Test method was evaluated. Results shows that proposed chitosan beads and their eco-friendly synthesis method can be applied in cell therapy and tissue engineering.
Keywords: Biocompatible Materials; antioxidancia; Antioxidants; mikrovlny; zvířata; Hydrogen-Ion Concentration; Animals; lidé; koncentrace vodíkových iontů; Cell Culture Techniques; chitosan; Microwaves; Mice; Cell Proliferation; Microspheres; proliferace buněk; Humans; Spectroscopy, Fourier Transform Infrared; myši; mikrosféry; biokompatibilní materiály; buněčné kultury; spektroskopie infračervená s Fourierovou transformací; Chitosan